School Phobia Revisited - Leard, Hugh M. (Canadian Journal of Counselling and Psychotherapy, 1972)
School phobia is the pronounced fear reaction of a child who is experiencing significant anxiety and suffering. Often, the mother of a phobic child has hampered his development by making him markedly dependent upon her. The child's needs have not been met in a consistent fashion and he has failed to develop a personal sense of security. The fear of separation from his mother is further complicated by a feeling of hostility towards her. This develops because of the mother's ambivalent handling of the child. The school becomes the focal point of his anxiety and hostility. Understanding the dynamics which underly this problem assists the counsellor or teacher to work more effectively with the child in the resolution of his problem. A warm accepting teacher is required. He must be one who can set firm and consistent yet reasonable limits for the child. Therapy is recommended for the child and his parents.